Pendampingan Masyarakat Dalam Program “Kampung Resik Lan Aman“ Untuk Mendorong Terciptanya Suatu Lingkungan Perkampungan Masyarakat Yang Berwawasan Lingkungan - Hamdan Hamdan; Muhamad Khalief Firmansyah; Nurul Ainaya Tohariah; Saroh Saroh; Vidlal Al Mubarok; Nofal Nofriyadi; Maulidiawati Maulidiawati; Dewi Mayang Sari; Ida Rahayu; Muhammad Dayat; Ikhsan Falaki; Wiwi Wiwi; Yayu Humairoh; Hoirul Rojikin; Atik Astari (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2023)
The Resik Lan Aman Village program is one of the programs launched by the Serang City Government since 2021 which aims to change people's behavior in order to create a clean and safe environment, but the community still does not really understand the purpose of this government program, so the Resik lan Aman Village competition, just a competition, this program does not foster understanding and awareness of the cleanliness and safety involved. The aim of this assistance is to provide an understanding of what a clean and healthy village environment looks like, the importance of safety and prevention. The results of this assistance show that not all residents of the Jakung Tengah neighborhood understand that the environment is clean and safe. Don't yet understand what facilities must be provided in a clean and safe village. However, after this assistance, residents' understanding is better and residents' awareness of environmental cleanliness and safety is better.